2017
DOI: 10.3389/fpls.2017.01208
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Alfalfa (Medicago sativa L.) Root-Symbiotic Rhizobia Responses under Alkali Stress

Abstract: Alkaline salts (e.g., NaHCO3 and Na2CO3) causes more severe morphological and physiological damage to plants than neutral salts (e.g., NaCl and Na2SO4) due to differences in pH. The mechanism by which plants respond to alkali stress is not fully understood, especially in plants having symbotic relationships such as alfalfa (Medicago sativa L.). Therefore, a study was designed to evaluate the metabolic response of the root-nodule symbiosis in alfalfa under alkali stress using comparative metabolomics. Rhizobium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 62 publications
2
45
1
Order By: Relevance
“…5c ) in transgenic lines compared with WT under bicarbonate alkaline stress. As shown previously, a great increase in MDA accumulation and POD activity is closely related to the responses of alfalfa to bicarbonate alkaline stress [ 35 , 36 ]. The transcriptional analysis also revealed the differential expression of alfalfa POD family genes under bicarbonate/carbonate alkaline stress [ 35 ].…”
Section: Discussionmentioning
confidence: 63%
“…5c ) in transgenic lines compared with WT under bicarbonate alkaline stress. As shown previously, a great increase in MDA accumulation and POD activity is closely related to the responses of alfalfa to bicarbonate alkaline stress [ 35 , 36 ]. The transcriptional analysis also revealed the differential expression of alfalfa POD family genes under bicarbonate/carbonate alkaline stress [ 35 ].…”
Section: Discussionmentioning
confidence: 63%
“…Metabolites, which are the end products of all cellular processes and the basis for phenotype expression, can affect gene transcription and protein expression in turn [52]. Furthermore, the metabolite responses of plants after inoculation with AMF under alkali stress included both plant-related and AM-related metabolites.…”
Section: Effects Of Arbuscular Mycorrhizal Fungi On the Metabolic Promentioning
confidence: 99%
“…and SCMRP genes into alfalfa demonstrated that the transgenic alfalfa displayed higher alkali tolerance [7]. And there is a research showed the physiologic mechanisms of enhanced resistance to alkali stress may be associated with increased antioxidant activity (via MDA, POD, SOD, and GSH), enhanced production of organic acids, and accumulation of osmolytes such as proline [13]. OsCu/Zn-SOD gene overexpression enhanced saline-sodic stress tolerance of O. sativa via increasing the detoxification capacity of reactive oxygen species in O. sativa and reducing salt-induced oxidative damage [14].…”
Section: Resultsmentioning
confidence: 99%